THE EFFECT OF PRICE, BRAND IMAGE, AND PROMOTION ON GABS CLOTHING PURCHASE DECISIONS AT MATAHARI DEPT STOREMOJOKERTO - Muhammad Dioda Zener Arindra S; Is Fadhilah; Anis Fitriyasari (Pedagogic Research-Applied Literacy Journal, 2026)
This study aims to analyze the influence of price, brand image, and promotion on purchasing decisions for Gabs brand clothing at Matahari Department Store Mojokerto. The research method used is quantitative with a sample of 92 respondents who are loyal customers. Data was collected through questionnaires and analyzed using multiple linear regression. The results of the study indicate that price has a positive and significant effect on purchasing decisions, with a significance value of 0.004. Brand image also has a significant positive effect with a significance value of 0.000. In addition, promotion is proven to be a dominant factor influencing purchasing decisions, with a significance value of 0.000. These findings indicate that companies need to improve their pricing strategies, strengthen their brand image, and conduct effective promotions to increase sales of Gabs products in the market. This study is expected to provide insights for entrepreneurs and further researchers in understanding the factors that influence consumer purchasing decisions.